2015
DOI: 10.1007/s00442-015-3398-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of precipitation change and neighboring plants on population dynamics of Bromus tectorum

Abstract: Shifting precipitation patterns resulting from global climate change will influence the success of invasive plant species. In the Front Range of Colorado, Bromus tectorum (cheatgrass) and other non-native winter annuals have invaded grassland communities and are becoming more abundant. As the global climate warms, more precipitation may fall as rain rather than snow in winter, and an increase in winter rain could benefit early-growing winter annuals, such as B. tectorum, to the detriment of native species. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 51 publications
3
38
0
1
Order By: Relevance
“…It has been widely postulated that many invasive plants will benefit more than natives in the face of anthropogenic change due to broader ecological tolerances, greater plasticity, greater affinity for disturbance, and/or better trait matching to novel conditions (Dukes & Mooney 1999;Hellmann et al 2008;Thuiller, Richardson & Midgley 2008;Walther et al 2009;Davidson, Jennions & Nicotra 2011;Sandel & Dangremond 2012). Some evidence suggests that exotic species may outperform natives under high resource conditions, particularly when they exhibit high resource acquisitive traits, while natives may perform better when resources are scarce (Daehler 2003;Levine et al 2003; van Kleunen, Weber & Fischer 2010;Blumenthal et al 2013;Prev ey & Seastedt 2015;Concilio et al 2015). However, exotic responses to resource influxes can be quite conditional (Eskelinen & Harrison 2014), and exotics can outperform natives under low resource conditions when they bear more 'resource use efficient' strategies than the natives (Funk & Vitousek 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely postulated that many invasive plants will benefit more than natives in the face of anthropogenic change due to broader ecological tolerances, greater plasticity, greater affinity for disturbance, and/or better trait matching to novel conditions (Dukes & Mooney 1999;Hellmann et al 2008;Thuiller, Richardson & Midgley 2008;Walther et al 2009;Davidson, Jennions & Nicotra 2011;Sandel & Dangremond 2012). Some evidence suggests that exotic species may outperform natives under high resource conditions, particularly when they exhibit high resource acquisitive traits, while natives may perform better when resources are scarce (Daehler 2003;Levine et al 2003; van Kleunen, Weber & Fischer 2010;Blumenthal et al 2013;Prev ey & Seastedt 2015;Concilio et al 2015). However, exotic responses to resource influxes can be quite conditional (Eskelinen & Harrison 2014), and exotics can outperform natives under low resource conditions when they bear more 'resource use efficient' strategies than the natives (Funk & Vitousek 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The direction of the effect depends on the context of the disturbance for both the focal exotic plant and the community it invades, including the disturbance history of the environment, the traits of the exotic plant, the season, frequency and duration of the disturbance (Crandall & Knight, ). Fewer studies have examined the role of competition with resident species (biotic resistance) in regulating population growth of exotic species, but those that have report that resident species may facilitate or compete with exotics (Crooks & Soulé, ; Griffith, ; Prevéy & Seastedt, ). Finally, studies examining the enemy release hypothesis have found significantly greater effects of herbivory on population growth rates of plants in their native compared to the invasive range (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies have examined the role of competition with resident species (biotic resistance) in regulating population growth of exotic species, but those that have report that resident species may facilitate or compete with exotics (Crooks & Soulé, 1999;Griffith, 2010;Prevéy & Seastedt, 2015). Finally, studies examining the enemy release hypothesis have found significantly greater effects of herbivory on population growth rates of plants in their native compared to the invasive range (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The continued rapid spread of B. tectorum threatens to displace > 40% of the current area of sagebrush steppe in the next 30 years (Chambers et al, 2007 and references therein). Climate change is likely to facilitate B. tectorum expansion into higher elevations by increasing habitat suitability or altering competitive constraints, thereby favoring B. tectorum over native species (Compagnoni and Adler, 2014;Dukes and Mooney, 1999;Prevey and Seastedt, 2015). Management of B. tectorum requires better knowledge of its response to ephemeral soil water content during the growing season.…”
Section: Introductionmentioning
confidence: 99%